Design of a glass climbing robot - NGUYEN, HUU PHUOC NGUYEN (Universiti Teknologi PETRONAS, 2007)
Wall-climbing robot is very useful in substituting human labors in dangerous and repetitive tasks like cleaning glass window in high building, maintenance, and inspection in industrial storage tank. A success in developing a climbing robot presents a huge economic benefit. This project aims to design a remote-controlled climbing robot that is able to operate on a vertical glass window. An effective adhesion mechanism using suction cups and solenoid valves had been designed. The locomotion mechanisms design based on a crossed-bar mechanism, utilizing pinion and rack. Detail drawings of the design and the robot specification had been finalized. A prototype was fabricated to demonstrate the design concept and its functionality. Control system of the robot, which includes an electrical circuit integrated with a C program, had been developed. Finally the functionality of the fabricated prototype was tested.